PEROKOK USIA DINI (STUDI KASUS SISWA SMP DESA KOTO SIMANDOLAK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI) - ", Dorisbon; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research examines the Early Age Smokers (Case Study of Junior High School Students in Koto Simandolak Village, Benai District, Kuantan Singingi Regency). Smoking behavior is a health problem because it can cause various diseases and even death. Smoking behavior among early childhood is usually influenced by positive feelings, with smoking a person feels the added positive taste. Juvenile delinquency is a behavior that exceeds the limits of the tolerance of other people or the surrounding environment as well as an action that can violate norms and laws. The characteristics of early smokers include intellectual, physical and psychological structures, and individual characteristics. The results of this study indicate that there are 4 factors that cause early smoking, including parents, peers, personality and mass media. Of the 4 factors the most dominant is the factor of father and peers so that from these two factors arise personality factors. Keywords: Smoking Behavior, Juvenile Delinquency, Early Age Smokers